Grafik Tasarım Öğrencilerinin Gözünden Tasarımcı Olmak Ve Tasarım Süreci - Aytaç ÖZMUTLU (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
Bu araştırmanın amacı grafik tasarım bölümü öğrencilerinin “tasarımcı olmak” ve “tasarım süreci”ne yönelik bakış açılarını incelemektir. Araştırmada nitel araştırma modeli içinde yer alan temel araştırma yöntemi benimsenmiştir. Araştırmanın çalışma grubu, amaçlı örnekleme yöntemi içinde yer alan ölçüt örnekleme yöntemi ile belirlenmiştir. Çalışma grubuna dâhil edilecek olan bireylerin belirlenmesinde grafik tasarım bölümünde öğrenim görmek ölçüt olarak belirlenmiştir. Grafik tasarım bölümünün 1, 2, 3 ve 4. sınıflarında öğrenim görmekte olan 45 lisans öğrencisi araştırmanın çalışma gurubunu oluşturmaktadır. Araştırma verileri, grafik tasarım bölümü öğrencilerinin tasarımcı olmak ve tasarım süreci konularına ilişkin düşüncelerini belirlemeyi amaçlayan yansıtıcı düşünme formu aracılığıyla toplanmıştır. Veri analizinde tekrarlı okuma ve karşılaştırmaların yapıldığı bir süreç takip edilmiştir. Grafik tasarım bölümü öğrencilerinin nitelikli bir tasarım sürecinin içeriğine, tasarımcı ve diğer insan farkına, tasarım sürecinin zorluklarına, tasarım sürecinde motive eden şeylere, tasarım öğrencisinin yapması gerekenlere ve nitelikli bir tasarımcıda bulunması gereken özelliklere ilişkin bakış açıları araştırmanın bulgular bölümünde kategorik yapılar altında özetlenmiştir. EXTENDED SUMMARY Background This research has been carried out in order to present the design process of graphic design students and their point of view to designers. This research provides the opportunity to examine the graphic design students' perspectives in categorical structures. In this respect, it will increase the awareness of graphic design educators about design students' perspectives on the field. This awareness will pave the way for a student-centered understanding in graphic design education. On the other hand, the research reveals how the design process of undergraduate students is experienced. These experiences will enable the design of methods, techniques and strategies in line with the research data on how graphic design education should be structured. Purpose In this research, the perspectives of graphic design students regarding being a designer and the design process are investigated. Within the scope of the research, the perspectives of graphic design students based on the following headings have been examined. a) The content of the qualified design process, b) The nature of the design process c) The designer and other human differences, d) The difficulties of the design process, e) Things that motivate the design process f) What the design student should do. Method In the research, the basic research method in the qualitative research model has been adopted. The answers to what and how questions are investigated with the basic research method. Since the aim of the study is to define the undergraduate students' perspectives on "graphic design process" and "being a graphic designer", graphic design students in 1st, 2nd, 3rd and 4th grades have been reached. In this context, 45 students have been determined as a study group. The research data have been collected through a reflective thinking form, which aims to determine graphic design students' thoughts about being a designer and the design process. Repeated reading and comparison process has been followed in the analysis of the data. Finding and Conclusion In this study, an explanation is made based on the design process of graphic design students and their perspective to the designer. In the research, first of all, the perspectives of graphic design students towards "components of a qualified design process" have been examined. This review shows that the components of a quality design process for students are to analyze in depth, sketch, focus, make timing and planning habits, focus on what they can do differently, and apply research and design principles. The students have stated that the difference between designers and non-designers stems from the perception process, problem solving, decision-making process, expression process, and lifestyle. In the study, graphic design students have explained 38 different characteristics related to the characteristics that a designer should have. The top three most frequently recurring features in the review appear to be creative, original, and current.